The Singaporean myth of meritocracy : perceptions of university experiences based on class lines - Tay, Rachel (2018)
This study interviewed and evaluated the lived, everyday experiences of university students. It reveals how individuals’ thoughts and actions are guided by Bourdieu’s concept of habitus, which refers to internalized dispositions derived from past experiences. Habitus is mitigated by constraints and opportunities found within the individual’s field of play, as well as resources or capital made accessible to the individual. In so doing, this paper reveals how habitus can work to either limit or enable an individual. This leads to inequalities that are obscured due to individuals’ individualization of successes and failures within an environment that perpetuates a fair and equitable discourse of meritocracy. Over time, individuals themselves help to perpetuate the meritocratic myth, having naturalized class differences and inequalities.